SPIDERS : WE'RE NOT SCARY WE'RE AMAZING! - Owen, Ruth; Sachner, Mark J. (Minneapolis, MN : Ruby Tuesday Books, 2024)
"These little eight-legged creatures are often the stuff of people's nightmares, but spiders are amazing animals that are essential for our world. Told from a spider's point of view, in this book spiders set out to convince their human doubters that they really aren't out to scare or harm people. In fact, they are far too busy weaving beautiful silk structures, hunting, keeping insect pests under control and raising their young to want to frighten humans."--
Includes index.
Keywords: Arachnida -- Juvenile literature; Insects -- Juvenile literature